PKM Pemanfaatan Batang Tembakau (Nicotiana Tabacum) sebagai Biopestisida di Bucor Wetan Pakuniran Probolinggo - Husnul Khotimah (Universitas Nurul Jadid, 2020)
Tobacco is one of the important agricultural commodities in Bucor Wetan Village, Pakuniran District, Probolinggo Regency. However, tobacco stems (nicotiana tobacum) are often considered as agricultural waste, since a lack of effective treatment is given to them. This community service activity is to utilize tobacco stem waste to be useful by making it a biopesticide to treat pests and diseases in plants. To achieve these goals, this program is by counseling and training to farmer groups on how to make biopesticides from tobacco stems. The results of this activity were: a) the participants’ enthusiasm is more considerable, especially the Farmer Group, to involve with the training, and b) their knowledge of using tobacco stems is more increased, since they have highly today’s economic value.